Managing Acquisitions: Creating Value Through Corporate RenewalManaging Acquisitions: Creating Value Through Corporate Renewal, by Haspeslagh Philippe C. Jemison David B.. New York: The Free Press, 1991, 416 pp., $29.95, cloth. - Rosenzweig, Philip M. (Academy of Management Review, 1993)
The article reviews the book “Managing Acquisitions: Creating Value Through Corporate Renewal,” by Philippe C. Haspeslagh and David B. Jemison.